Challenges and limitations in secure software development adoption - A qualitative analysis in Malaysian software industry prospect - Ahmed Maher, Zulfikar; Shah, Asadullah; Chandio, Shahmurad; Mohd Mohadis, Hazwani; Abd Rahim, Noor Hayani (Indian Society for Education and Environment, 2020)
Inclusion of security in software development from the initial design phase has not been consistently addressed by the software developers. As a result there is an abundance of software systems with weak security. The objective of this study is to find out factors influencing developer's intention to adopt secure software development practices. Methodology: This study is based on qualitative research methodology. Interviews were conducted from the professionals working at senior positions at Malaysian software development organization. All the interviews were first transcribed, as they were digitally recorded. Then transcribed data was analyzed in a way that all frequent words or repetitive concepts were highlighted, after which many similar or relevant concepts were grouped together and categorized as themes and sub themes. Findings: The data was analyzed using the thematic analysis method. The results revealed five main themes, whereas each main theme has sub-themes. These sub-themes are parameters to justify the main theme. Main themes were identified in the light of the interviewee's response. The main results include interviewee's demographic characteristics, and then the main themes identified include, Adoption of SSD practices, Influencing authorities, Motivating Factors, Attitude towards SSD, Hindrances / Issues towards SSD Adoption. Sub themes included: Security Culture, Change Management, Applications of SSD, Managers, Security Expert, Training, Incentives, Security Awareness, Performance Expectancy, Facilitating Conditions, Demographic Characteristics, Need to use SSD, No clear guidelines, Strict Project Timeline, Lack of Security knowledge. The overall interview results show that secure software development practices adoption level in most part of the software industry is not up to the satisfactory level. Novelty/Applications: This research explores the factors impeding the implementation of the best security practices, and barriers to secure software development practices adoption. This study can be used as guideline to be followed for the implementation of secure software development practices in software industry. Keywords: Secure software development adoption; organizational factors;software developer intention; security development; software security.